Odpowiedź:
2x - 3 + 5x = 3x - 7
7x - 3x = -7 + 3
4x = -4 /:4
x = -1
2,5x - 3,5 = 4,5
2,5x = 4,5 + 3,5 /:2,5
x = 8 : 2,5 = 3,2
-0,09x + 0,4 = 0,06
-0,09x = 0,06 - 0,4 /:(-0,09)
x = -0,34 : (-0,09) = 34/9 = 3 7/9
12x - 4 + 14x - 5 = 12x - 6
26x - 12x = -6 + 9
14x = 3 /:14
x = 3/14
2/3x - 3/4 = 2/3
2/3x = 2/3 + 3/4 /*3/2
x = 3/2(8/12 + 9/12) = 3/2 * 17/12 = 17/8 = 2 1/8
-12x - 14 - 2x = -3x - 5
-14x + 3x = -5 + 14
-11x = 9 /:(-11)
x = -9/11
2/3x + 1/3x - 4/5 = 6/5
x = 6/5 + 4/5 = 10/5 = 2
4x + 15 - 29x - 130 = 67x - 5
-25x - 67x = -5 + 115
-92x = 110 /:(-92)
x = -110/92 = -1 18/92 = -1 9/46
Szczegółowe wyjaśnienie: